PENGARUH LEARNING STARTS WITH A QUESTION (LSQ) TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII SMP ISLAM SA’ADATUDDARAIN NW MAJUWET TAHUN PELAJARAN 2019/2020 - didi kuswara (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2020)
The purpose of the study was to determine the effect of the Learning Starts With A Question (LSQ) model on learning outcomes of Class VIII students of the Islamic Junior High School of Sa'adatuddarain NW Majuwet 2019/2020 school year. This type of research is quasi-experimental. The research design used was a post test only control design. The population in this study were all students of class VIII Islamic Junior High School of Sa'adatuddarain NW Majuwet in Academic Year of 2019/2020. The samples were all students of VIIIth grade in amounts of 41 students which had been divided into 2 classes. VIII A class amounting to 21 people as an experimental class while VIIIB class, amounting to 20 students as a control class. The independent variable in this study was the application of the LSQ (Learning Start with a Question) model while the dependent variable was the learning outcomes. Based on the results of the study, the average value of student learning outcomes with the application of LSQ of 76,19 while with the conventional method of 66,25. Based on the hypothesis test using the t test that is tcount = 4.86>ttable = 2.04. Thus, from the results of the study above, it can be concluded that the learning model of learning start with a question has a significant effect on learning outcomes of students of class VIII of Islamic Junior School Sa'addatuddarain of NW Majuwet.